2023
DOI: 10.3390/antibiotics12111630
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hygiene Protocols on the Mechanical and Physical Properties of Two 3D-Printed Denture Resins Characterized by Extrinsic Pigmentation as Well as the Mixed Biofilm Formed on the Surface

Adriana Barbosa Ribeiro,
Beatriz Marcatto Tinelli,
Lorena Mosconi Clemente
et al.

Abstract: To assess the effect of hygiene protocols and time on the physical–mechanical properties and colony-forming units (CFU) of Candida albicans, Staphylococcus aureus, and Streptococcus mutans on 3D-printed denture resins (SmartPrint and Yller) with extrinsic pigmentation compared to conventional resin (CR). The protocols were evaluated: brushing (B), brushing and immersion in water (W), 0.25% sodium hypochlorite (SH), and 0.15% triclosan (T), simulating 0, 1, 3, and 5 years. The data were analyzed by ANOVA with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In addition to the development of products and methods that aim to reduce the microbial load and prevent DRS, technological development also provides new materials for application in the manufacture of prostheses, such as additive manufacturing (printed) and subtractive manufacturing resins. Aiming to evaluate the behavior of these materials in the face of biofilm formation, and their physical–mechanical behavior when exposed to different environmental factors and hygiene protocols, some in vitro studies have been carried out [ 116 , 129 , 130 , 131 , 132 , 149 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the development of products and methods that aim to reduce the microbial load and prevent DRS, technological development also provides new materials for application in the manufacture of prostheses, such as additive manufacturing (printed) and subtractive manufacturing resins. Aiming to evaluate the behavior of these materials in the face of biofilm formation, and their physical–mechanical behavior when exposed to different environmental factors and hygiene protocols, some in vitro studies have been carried out [ 116 , 129 , 130 , 131 , 132 , 149 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this context, an experimental study observed that the use of brushing combined with 0.25% sodium hypochlorite for 20 min effectively reduced the microbial load of multispecies biofilm. However, they noted that the printed resins experienced alterations in their physical–mechanical properties when evaluated over a simulated period of 5 years [ 149 ]. Consequently, caution is warranted when recommending the prolonged use of these resins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations